Flexible CO2-plume geothermal (CPG-F): Using geologically stored CO2 to provide dispatchable power and energy storage. (1st February 2022) - Fleming, Mark R.; Adams, Benjamin M.; Ogland-Hand, Jonathan D.; Bielicki, Jeffrey M.; Kuehn, Thomas H.; Saar, Martin O.
Highlights: Introduce Flexible CO2 -Plume Geothermal (CPG-F) facilities. CPG-F can provide dispatchable power, energy storage, or both simultaneously. There are multiple optimum design points that may be in tension with one another. Abstract: CO2 -Plume Geothermal (CPG) power plants can use geologically stored CO2 to generate electricity. In this study, a Flexible CO2 Plume Geothermal (CPG-F) facility is introduced, which can use geologically stored CO2 to provide dispatchable power, energy storage, or both dispatchable power and energy storage simultaneously—providing baseload power with dispatchable storage for demand response. It is found that a CPG-F facility can deliver more power than a CPG power plant, but with less daily energy production. For example, the CPG-F facility produces 7.2 MWe for 8 h (8 h-16 h duty cycle), which is 190% greater than power supplied from a CPG power plant, but the daily energy decreased by 61% from 60 MWe -h to 23 MWe -h. A CPG-F facility, designed for varying durations of energy storage, has a 70% higher capital cost than a CPG power plant, but costs 4% to 27% more than most CPG-F facilities, designed for a specific duration, while producing 90% to 310% more power than a CPG power plant. A CPG-F facility, designed to switch from providing 100% dispatchable power to 100% energy storage, only costs 3% more than a CPG-F facility, designed only for energy storage.